Analisis Daya Dukung Tanah Pondasi Berdasarkan Data Uji Cone Penetration Test - Ripdatul Hasanah; Fatma Sarie; Mohammad Ikhwan Yani (Fakultas Teknik, 2023)
In construction work, foundation planning must be appropriately designed so that the stresses in the foundation do not exceed the bearing capacity of the soil below. This study aims to determine the bearing capacity of the soil using the Terzaghi method, the Meyerhof method, and the Hansen method as well as to analyze the safety of the A3 building design on Yos Sudarso Induk Street, Palangka Raya City. The calculation results show that the Terzaghi value is lower than the Meyerhof and Hansen methods. The Terzaghi method obtained 375.567 kN/m2, the Meyerhof method obtained 1105.396 kN/m2 and the Hansen method obtained 848.996 kN/m2. At the 3 bridge points reviewed, the stress that appears on the pavement base at point C3 is 170.923 kN/m2 soil bearing capacity, point D3 is 160.90 kN/m2 soil bearing capacity and point C6 is 159.421 kN/m2 bearing capacity soil load. The third train point is declared safe because the voltage at the base of the guitar is lower than the load capacity of the ground.